Examining the tsetse teneral phenomenon and permissiveness to trypanosome infection - Haines, L R (Frontiers in Cellular and Infection Microbiology, 2013)
Tsetse flies are the most important vectors of African trypanosomiasis but, surprisingly, are highly refractory to trypanosome parasite infection. In populations of wild caught flies, it is rare to find mature salivarian and mouthpart parasite infection rates exceeding 1% and 15%, respectively. This inherent refractoriness persists throughout the lifespan of the fly, although extreme starvation and suboptimal environmental conditions can cause a reversion to the susceptible phenotype. The teneral phenomenon is a phenotype unique to newly emerged, previously unfed tsetse, and is evidenced by a profound susceptibility to trypanosome infection. This susceptibility persists for only a few days post emergence and decreases with fly age and bloodmeal acquisition. Researchers investigating trypanosome-tsetse interactions routinely exploit this phenomenon by using young, unfed (teneral) flies to naturally boost trypanosome establishment and maturation rates. A suite of factors may contribute, at least in part, to this unusual parasite permissive phenotype. These include the physical maturity of midgut barriers, the activation of immunoresponsive tissues and their effector molecules, and the role of the microflora within the midgut of the newly emerged fly. However, at present, the molecular mechanisms that underpin the teneral phenomenon still remain unknown. This review will provide a historical overview of the teneral phenomenon and will examine immune-related factors that influence, and may help us better understand, this unusual phenotype.